Aberrant Cerebral Blood Flow in Response to Hunger and Satiety in Women Remitted from Anorexia Nervosa - Wierenga, Christina E.; Bischoff-Grethe, Amanda; Rasmusson, Grace; Bailer, Ursula F.; Berner, Laura A.; Liu, Thomas T.; Kaye, Walter H. (Frontiers in Nutrition, 2017)
The etiology of pathological eating in anorexia nervosa (AN) remains poorly understood. Cerebral blood flow (CBF) is an indirect marker of neuronal function. In healthy adults, fasting increases CBF, reflecting increased delivery of oxygen and glucose to support brain metabolism. This study investigated whether women remitted from restricting-type AN (RAN) have altered CBF in response to hunger that may indicate homeostatic dysregulation contributing to their ability to restrict food. We compared resting CBF measured with pulsed arterial spin labeling (ASL) in 21 RAN and 16 healthy comparison women (CW) when hungry (after a 16 hour fast) and after a meal. Only remitted subjects were examined to avoid the confounding effects of malnutrition on brain function. Compared to CW, RAN demonstrated a reduced difference in the Hungry minus Fed CBF contrast in the right ventral striatum, right subgenual anterior cingulate cortex (pcorr<0.05) and left posterior insula (punc<0.05); RAN had decreased CBF when hungry vs fed whereas CW had increased CBF when hungry vs fed. Moreover, decreased CBF when hungry in the left insula was associated with greater hunger ratings on the fasted day for RAN. This represents the first study to show that women remitted from AN have aberrant resting neurovascular function in homeostatic neural circuitry in response to hunger. Regions involved in homeostatic regulation showed group differences in the Hungry minus Fed contrast, suggesting altered cellular energy metabolism in this circuitry that may reduce motivation to eat.